Iodine Content in Breast Milk Samples in the Aegean Region in Turkey - AVCIBASI, UGUR; ALTUNATA, TURHAN (Asian Journal of Chemistry, 2010)
In this study, the iodine content in breast milk was measured by Sandell-Kolthoff's method. The milk was obtained from 40 healthy mothers, aged 20 to 37, from the pediatric division of Ege University hospital. All mothers were from Aegean region of Turkey. Comparisons were made with commercial milk samples. Destruction of organic matter by using alkaline ash method was carried out prior to determination by Sandell-Kolthoff reaction based on iodine's catalytic effect on the Ce(IV)-As(III) system. The iodine concentration ranges were within 19.1 and 94.2 μg/kg in breast milk samples. Results obtained in this study clearly showed that breast milk samples did not have iodine deficiency which can lead to goiter and iodine concentrations of market milk were at sufficient level in the Aegean region of Turkey.